Etnomathematics: Exploration Tapis Lampung on Two-Dimentional Figure and Social Arithmetics - Lisnani, L; Yuningrum, Theresia; Suyono, Agus (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe ethnomathematics activities in the manufacturing process, explain the two-dimensional figure, and describe the introduction of social arithmetic through motifs on Tapis Lampung. The sample in this study is the home craftsman and homeowners of Tapis Lampung production. This type of research is a qualitative study using an ethnographic approach, where research is conducted to explore human behavior that occurs in certain cultures. The data collection technique is by interview, observation, and documentation. The results of this study are as follows: 1) the existence of ethnomathematics activity in the manufacture of Tapis Lampung; 2) on six motifs of Tapis Lampung in which there are two-dimensional figures, namely square, triangle, trapezoidal, rectangular, rhombus, kite, and circle; 3) based on the size and results of the final product of Tapis Lampung, a mathematical topic is found, namely social arithmetic at the sale price.